Effect of total abdominal hysterectomy on ovarian blood supply in women of reproductive age - Nahás, Eliana Aguiar Petri [UNESP] (2005)
Objective. The purpose of this study was to evaluate the effect of total abdominal hysterectomy on ovarian blood supply using transvaginal color Doppler ultrasonography in women of reproductive age. Methods. This prospective study included 61 women aged 40 years or younger who were divided into 2 groups: group 1, comprising 31 patients who underwent total abdominal hysterectomy (TAH); and group 2, comprising 30 women with no abnormalities. Inclusion criteria included normal ovarian function at baseline, with basal follicle-stimulating hormone levels of less than 15 mUl/mL, normal body weight, no tobacco use, and no history of laparotomy or ovarian disease. Ovarian arterial blood supply by determination of the pulsatility index (PI) on Doppler analysis and ovarian volume on transvaginal ultrasonography were assessed at baseline and at 6 and 12 postoperative months. The Student t test, profile analysis, and Friedman and Mann-Whitney tests were used in the statistical analysis of data. Results. Statistical analysis of baseline data revealed that both groups were homogeneous. At months 6 and 12, greater ovarian volumes and lower Pl values were observed in patients who underwent TAH (P < .05). By the end of the study, in 8 of the 31 patients who underwent TAH (25.5%), benign ovarian cysts were observed. In the control group, all the parameters studied remained unchanged. Conclusions. The reduced PI values observed on Doppler ultrasonography suggested a decrease in the resistance flow in the ovarian arteries in women of reproductive age who underwent TAH.